(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
The present study aims at optimization of a suitable mass production technology for growth and sporulation of the biocontrol agents Verticillium lecanii and Trichoderma harzianum. Combinations of various natural solid substrates (Rice, Maize, Arhar, Defatted Soybean, Gram) and laboratory media (SMYA, Complete media, SDA, Czapek’s Dox media ) were evaluated for growth and sporulation of V. lecanii and T. harzianum. Data on CFU, concentration of propagules, dry mycelial weight, conidia production and conidia yield were analyzed. It was observed that among the substrate types tested, the fungal strains grew better and produced high quantity of spores in Rice as growth medium after 21 days of incubation followed by Maize and Arhar. The best liquid media which supported maximum conidial production was SMYA and Complete medium. Also, rate of germination of spores as well as their viability at different aeration rates was tested. It was observed that maximum length of germ tube in minimum duration was observed in Rice as substrate. The viability percentage of the biocontrol agents produced at various aeration rates and agitation speeds showed that change in aeration and agitation did not significantly affect spore viability. Results demonstrated that the fungal species could be rapidly produced with a high conidial yield on natural solid substrates as compared to liquid media by fermentation technology.